Spatio-temporal variability in the strength, directionality, and relative importance of climate on occupancy and population densities in a philopatric mammal, the American pika (Ochotona princeps) - Billman, Peter D.; Beever, Erik A.; Westover, Marie L.; Ryals, Dylan K. (Frontiers in Ecology and Evolution, 2023)
Species distribution models (SDMs) have been widely employed to predict species-environment relationships. However, when extrapolated over broad spatial scales or through time, these models decline in their predictive ability, due to variation in how species respond to their environment. Many models assume species-environment relationships remain constant over space and time, hindering their ability to accurately forecast distributions. Therefore, there is growing recognition that models must account for spatio-temporal non-stationarity -- a phenomenon wherein the factors governing ecological processes change over space or time. Here, we investigated non-stationarity in American pika (Ochotona princeps) relationships with climatic variables in the Rocky Mountains (USA). We first compared broad-scale differences in pika-climate patterns for occupancy and population density across the Southern, Central, and Northern Rockies. Next, we investigated within-ecoregion variation across four mountain ranges nested within the Northern Rockies. Lastly, we tested whether species-climate relationships changed over time within the Central Rockies ecoregion. Across all analyses, we found varying levels of non-stationarity among the climate metrics for both pika occupancy and density. Although we found general congruence in temperature metrics, which consistently had negative coefficients, and moisture metrics (e.g., relative humidity), which had positive coefficients, non-stationarity was greatest for summer and winter precipitation over both space and time. These results suggest that interpretations from one ecoregion should not be applied to other regions universally, especially when using precipitation metrics. The within-ecoregion analysis found greater variation in the strength-of-relationship coefficients among the four mountain ranges, relative to the inter-regional analysis, possibly attributable to smaller sample sizes per mountain range. Lastly, the importance of several variables shifted through time from significant to insignificant. Our results collectively reveal the overall complexity underlying species-environment relationships. With rapidly shifting conditions globally, this work adds to the growing body of literature highlighting how issues of spatio-temporal non-stationarity will limit the accuracy, transferability, and reliability of models and that interpretations will likely be most robust at local to regional scales. Diagnosing, describing, and incorporating non-stationarity of species-climate relationships into models over space and time will be pivotal for creating more informative models.